Identifikasian Risiko - Herbi okta riansi (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2023)
Some risks are more important than other risks. Whether or not a particular risk matters depends on the nature of the risk, its effect on the particular activity and the criticality of the activity. To reduce the hazard, there must be guarantees to minimize the risk or at least distribute it during the development and ideally the risk is removed from activities that have a critical path.